Lexington (Merchant vessel) logbook - Lexington (Merchant vessel)
Logbook of the American merchant vessel Lexington, of Baltimore, Md., kept on a voyage from New York, N.Y., to Bremen, Germany, and on the return voyage from Amsterdam, Netherlands, to Baltimore. Timothy Gardner was shipmaster.
Keywords: Gardner, Timothy; Merchant marine -- Maryland -- Baltimore; Ports of entry -- Maryland -- Baltimore; Ports of entry -- Netherlands -- Amsterdam; Ports of entry -- New York (State) -- New York; Ship's papers -- 19th century; Baltimore (Md.) -- History